Research on Excavation and Support Technology for Large Deformation Sections of Soft Rock in Highway Tunnels - Zeng, Xintao; Mao, Liang (Journal of Theory and Practice of Management Science, 2023)
The stability of the surrounding rock in the large deformation section of soft rock is poor, which brings difficulties to the construction of highway tunnels. As early as the Ninth Five Year Plan period, research was conducted on the construction technology of large deformation soft rock tunnels, and a large number of research results were obtained and applied to the construction of tunnel engineering. In the deformation process of soft rock Roadworks construction for large tunnels, it is easy to produce large deformation, even collapse, roof collapse and other accidents. It is necessary to carry out detailed Geological survey, reasonable support parameters, and do a good job in quality control during the construction process to effectively improve the deformation of soft rock, control the deformation of surrounding rock, and ensure the safety and stability of the tunnel support structure.